2016
DOI: 10.1016/j.ajpath.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

p15 Expression Differentiates Nevus from Melanoma

Abstract: Most melanomas are driven by BRAF(V600E)-activating mutations, while nevi harboring the same mutations have growth arrest. Although decreased p16 expression has been associated with melanoma formation, in recent work, p15 represented a primary effector of oncogene-induced senescence in nevomelanocytes that was diminished in melanomas. This study determined whether decreased p15 levels represent a general biomarker for the transition from nevus to melanoma. We performed p15 and p16 IHC analyses on a random seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
11
0
3
Order By: Relevance
“…Our study confirms an observation from prior studies, that p15 is expressed not only in melanocytes but in epithelial tissues (Figure A,C, and Figure C,F). We observed higher levels of p15 than p16 expression in epidermal keratinocytes, outer root sheath keratinocytes and adnexal epithelium in this study as well as in prior studies . Previous studies have indicated that p15 mRNA and protein expression are higher in epithelial cells than p16 under most experimental conditions .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our study confirms an observation from prior studies, that p15 is expressed not only in melanocytes but in epithelial tissues (Figure A,C, and Figure C,F). We observed higher levels of p15 than p16 expression in epidermal keratinocytes, outer root sheath keratinocytes and adnexal epithelium in this study as well as in prior studies . Previous studies have indicated that p15 mRNA and protein expression are higher in epithelial cells than p16 under most experimental conditions .…”
Section: Discussionsupporting
confidence: 82%
“…We observed higher levels of p15 than p16 expression in epidermal keratinocytes, outer root sheath keratinocytes and adnexal epithelium in this study as well as in prior studies. 29,30 Previous studies have indicated that p15 mRNA and protein expression are higher in epithelial cells than p16 under most experimental conditions. 34,35 Therefore, the increased epidermal and adnexal epithelial staining may represent the fact that p15 is more highly expressed in epithelial cells than p16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This locus may be important not only because of p16, but also because it is the locus of 2 other tumor suppressors, p14 and p15, which have relevance to melanoma progression. 108 In one study, TERT promoter mutations were highly associated with fatal outcomes. 109 The sensitivity, specificity, and predictive value of these features and tests have in general not been tested and this is difficult because appropriate gold standards do not exist.…”
Section: Pathway I: Low-csd Melanoma/superficial Spreading Melanomamentioning
confidence: 99%